Key contemporary buildings : plans, sections and elevations. - Gregory, Rob, ....- (London : Laurence King, 2008)
Featuring 95 of the most significant buildings of the early twenty-first century, this book includes works by such eminent architects as Renzo Piano, Norman Foster, OMA and Frank Gehry, as well as newer names, such as Jamie Fobert and Sou Fujimoto. The buildings are organized by planning strategy and are divided into eight chapters, each with an informative introduction that ties the buildings back to iconic examples from the twentieth century. For each building there are numerous, accurate scale plans showing a combination of floor plans, elevations and sections as appropriate, all specially redrawn for this book and based on the most up-to-date information and sources. For each of the buildings there is a concise text discussing the organizational strategy and the significant architectural features of the buildings anatomy, together with colour images. The quality and number of the line drawings, together with the authoritative text and images, allow all the buildings to be understood in detail
Keywords: Bouwkunst